Thalassomya gutae sp. n., a new marine chironomid (Diptera: Chironomidae: Telmatogetoninae) from the Brazilian coast - de Oliveira, Caroline Silva Neubern; Da Silva, Fabio Laurindo; Trivinho-Strixino, Susana (Zootaxa, 2013)
One new species of Thalassomya Schiner, 1856 (Diptera: Chironomidae: Telmatogetoninae), T. gutae sp. n. is described and figured as male, pupa and larva. The specimen was collected in the marine zone between tide-marks, in southeastern Brazilian coast and is the first species of this genus recorded to Brazil.